Guatemala: The impact of COVID-19 and preliminary implications: Interim report - Díaz-Bonilla, Eugenio; Laborde Debucquet, David; Piñeiro, Valeria (International Food Policy Research Institute, 2021)
As most countries in the world Guatemala has been affected by COVID-19. In January 2020 the country decreed travel bans from China, which were later expanded to other countries. Still, Guatemala had the first confirmed COVID case in March 13 and the first death in March 15. Some days before that, on March 5, the government had declared the “state of calamity” (Declaración del Estado de Calamidad Pública - Decreto Gubernativo Número 5-2020), which allowed the government to limit different rights, and to take different actions to protect the health and safety of all persons in Guatemala. This brief covers the following topics until the time of this report. First, it shows the evolution of the pandemic, using different indicators. Second, it summarizes the main responses and costs and financing. Third, it shows some actual impacts with available data up to the time of this writing. Fourth, the modeling framework for the simulations is briefly presented. Fifth, the document pre